Urinary 8-hydroxy-2′-deoxyguanosine levels and preterm births: a prospective cohort study from the Japan Environment and Children’s Study - Zentaro Yamagata; Mitsuaki Hosoya; Hiroyasu Iso; Takeo Nakayama; Reiko Kishi; Nobuo Yaegashi; Shuichi Ito; Koichi Kusuhara; Hidekuni Inadera; Michihiro Kamijima; Yukihiro Ohya; Koichi Hashimoto; et al. (BMJ Open, 2024)
Objectives To evaluate the association between urinary 8-hydroxy-2′-deoxyguanosine (U8-OHdG) level—a marker of oxidative stress—and the incidence of preterm births (PTBs).Design Prospective cohort study.Setting The Japan Environment and Children’s Study (JECS).Participants Data from 92 715 women with singleton pregnancies at and after 22 weeks of gestation who were enrolled in the JECS, a nationwide birth cohort study, between 2011 and 2014 were analysed. U8-OHdG levels were assessed once in the second/third trimester using liquid chromatography–tandem mass spectrometry. Participants were categorised into the following three or five groups: low (<1.95 ng/mg urinary creatinine (Cre)), moderate (1.95–2.94 ng/mg Cre) and high (≥2.95 ng/mg Cre) U8-OHdG groups, or groups with <1.87, 1.87–2.20, 2.21–2.57, 2.58–3.11 and ≥3.12 ng/mg Cre. For stratification, participants with representative causes for artificial PTB were excluded.Primary and secondary outcome measures Adjusted OR (aOR) for PTB before 37 and 34 weeks of gestation were calculated using a multivariable logistic regression model while adjusting for confounding factors; the moderate or lowest U8-OHdG group was used as the reference, respectively.Results The aORs for PTB before 37 weeks of gestation in the high U8-OHdG group were 1.13 (95% CI 1.05 to 1.22) and 1.13 (95% CI 1.04 to 1.23) after stratification. The aOR for PTB before 37 weeks in the fourth group was 0.90 (95% CI 0.81 to 0.99). After stratification, the aORs for PTB before 37 and 34 weeks in the fifth group were 1.15 (95% CI 1.03 to 1.29) and 1.46 (95% CI 1.08 to 1.97), respectively.Conclusions High U8-OHdG levels were associated with increased PTB incidence, especially in participants without representative causes for artificial PTB. Our results can help identify the mechanisms leading to PTB, considering the variable aetiologies of this condition; further validation is needed to clarify clinical impacts.